The Role of Civics Teachers in Differentiated Learning with Problem Based Learning to Realize a Project to Strengthen the Profile of Pancasila Students - Dirgantoro, Ajar; Ajis, Mohammad Choirul ajis (JURNAL MANAJEMEN MUTU PENDIDIKAN, 2024)
Education plays a major role in a person's life, because education allows the development of individual potential and abilities to determine their future. Teachers play an important role in teaching, guiding, and encouraging students. This research was conducted with a qualitative approach in a natural environment. It aims to reveal the phenomena that occur in the field through a descriptive research design that uses written and oral conversations between the author and informants. Based on the results of interviews conducted by the researcher, it was found that differentiated learning using the Problem Based Learning model, especially in PPKn subjects in class VII, made students happier and more interested because the role of the teacher, especially in PPKn subjects, made students enthusiastic in learning because the role of the teacher as a motivator greatly influenced the teaching and learning process. Based on these results, it can be concluded that the use of Problem Based Learning in differentiated learning in PPKn subjects has proven to be effective in the learning process.Keywords: the role of the teacher, differentiation, problem based learningDOI: 10.23960/jmmp.v12.i2.2024.30325